2017
DOI: 10.1055/s-0043-114008
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Incremental Sit-to-Stand Exercise for Aerobic Fitness Evaluation

Abstract: Incremental sit-to-stand exercise (ISTS) is an incremental exercise test using external signals to control the sit-to-stand rate in a given time frame. This study aimed to investigate the concurrent validity and reproducibility of the ISTS in aerobic fitness evaluation among healthy elderly women. Sixteen elderly women performed the ISTS and cycle ergometer test at 3-day to 2-week intervals, and six of the participants performed the ISTS twice. Peak oxygen uptake (VO), peak heart rate and completion time on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 23 publications
0
7
1
Order By: Relevance
“…The linear regression equation obtained in this study to predict peak VO 2 based on the ISTS performance differs from that among healthy older people in our previous study: peak VO 2 of the ISTS test in T2DM older patients (mL/ min/kg) = 0.0216 × the ISTS completion time (S) + 4.7318 (Fig. 2), compared with peak VO 2 of the ISTS test in healthy older people (mL/min/kg) = 0.02 × the ISTS completion time (S) + 9.6 (Nakamura et al 2017). The difference predicts a lower peak VO 2 based on the same ISTS performance among older patients with T2DM than that among healthy older people.…”
Section: Validity Of the Ists Testcontrasting
confidence: 67%
See 4 more Smart Citations
“…The linear regression equation obtained in this study to predict peak VO 2 based on the ISTS performance differs from that among healthy older people in our previous study: peak VO 2 of the ISTS test in T2DM older patients (mL/ min/kg) = 0.0216 × the ISTS completion time (S) + 4.7318 (Fig. 2), compared with peak VO 2 of the ISTS test in healthy older people (mL/min/kg) = 0.02 × the ISTS completion time (S) + 9.6 (Nakamura et al 2017). The difference predicts a lower peak VO 2 based on the same ISTS performance among older patients with T2DM than that among healthy older people.…”
Section: Validity Of the Ists Testcontrasting
confidence: 67%
“…The ISTS is a simpler and more cost-effective test because it can be performed in a small space using a chair; moreover, the physical load intensity can be easily adjusted by changing the standing up and sitting down speed (Nakamura et al 2016). In a previous study, the ISTS was found to be a valid, reproducible test to evaluate the physical capacity of healthy older women, and it could be performed safely (Nakamura et al 2017). However, to the best of our knowledge, the ISTS has not been validated for older patients with T2DM.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations